11 Prevalence and Severity of Obstructive Sleep Apnea (OSA) in Men with Testosterone Deficiency (TD). Issue 1 (1st April 2022) - Salter, C; Flores, J; Schofield, E; Tan, M; Mulhall, J
ABSTRACT: Introduction: OSA is a common condition in the general population. Since untreated OSA can contribute to elevated hematocrit (HCT) levels and other negative health consequences, there may be value to screening men prior to initiation of testosterone therapy (TTH). Objective: The purpose of this study was to describe OSA rates in men with TD prior to initiation of TTH. Methods: This ongoing study included men seen in a sexual medicine clinic with TD. They were asked to complete two screening questionnaires for daytime sleepiness and OSA, respectively: the Epworth Sleepiness Scale (ESS) and the STOP-BANG (SB). ESS ranges from 0-24 and SB 0-8. Men whose scores indicated intermediate to high risk of OSA were advised to undergo a diagnostic sleep study which evaluated apnea hypoxia index (AHI, normal <5 events/h), total duration SpO2 saturation <88% and SpO2 nadir. Descriptive statistics are presented. Results: 152 men have completed the questionnaires with a mean age of 62±10 years. Baseline total T level was 296±103 ng/dL, baseline HCT was 43±4%. Median SB score was 4 (IQR 3-6). Median ESS score was 5 (IQR 3-8). 58% screened positive for OSA and were referred for sleep study; 88% of sleep studies resulted in a diagnosis of OSA. Mean AHI of the group was 19±14 events/hour (range 0.7-54.3 events/hour) with 52% having moderate or severe OSA (AHI >15/hour). SpO2 nadir was 80±7% (range 63-90%) with 67% having a nadir in the 80s, 24% in the 70s and 10% in the 60s. Mean total duration SpO2 ≤88% was 25±32 minutes (range 0.1-151.6 minutes) with 47% of men <10 minutes and 6% >80 minutes. Conclusions: These data demonstrate that about half of men with TD screen positive for OSA using the SB questionnaire and the vast majority of them were formally diagnosed with OSA. Given the health risks associated with untreated OSA, especially developing polycythemia on TTH, we advocate screening such men for OSA prior to commencement of TTH. Disclosure: No